Zu zwei Verbindungen des Altägyptischen mit der Beja-Sprache - Bojowald, Stefan (AAeO - Afrikanistik-Aegyptologie-Online, 2023)
In this article two parallels between the Ancient Egyptian and the Beja language are discussed. In the first case, the connection between ear of corn and thorn is investigated. In the second case, the Beja root sir ‘wooden shaft of the spear’ is compared with the Ancient Egyptian root śr.t ‘thorn’.